PENGARUH MODEL PEMBELAJARAN DIRECT INSTRUCTION TERHADAP KEMAMPUAN TEKNIK DASAR SEPAK BOLA SISWA SEKOLAH MENENGAH KEJURUAN - Ipangsyah, Mohamad; Ega Trisna Rahayu; Asep Suherman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examined the effect of the Direct Instruction model on the basic soccer skills of Grade X students at SMK Pandu 2 Ciampea. The study was motivated by students’ limited mastery of passing, dribbling, and shooting and by a learning process that had not yet provided sufficiently systematic demonstrations, guided practice, and corrective feedback. A quantitative pre-experimental approach with a one-group pretest-posttest design was used. The sample consisted of 32 students selected through cluster random sampling. Performance tests assessed the preparation, execution, and follow-through phases of passing, dribbling, and shooting. Data were analyzed using the Shapiro-Wilk normality test, a homogeneity test, and paired-samples t-tests with SPSS 27. The statistical output indicated that the data met the parametric assumptions and that post-intervention performance differed significantly from pre-intervention performance for all three skills (p < .001). The findings show that Direct Instruction can support the acquisition of structured motor skills when the teacher presents clear models, organizes practice progressively, checks performance continuously, and provides immediate feedback. The model is therefore relevant as an instructional option for basic soccer learning in vocational secondary schools, while future studies should use a control group and retention measures.